Ứng dụng thuật toán tự thích nghi gạt giao thoa trong kênh pha đinh lựa chọn - Nam, Nguyễn Hoài (Journal of Computer Science and Cybernetics, 2016)
Interference fading is one of the reason that causes the intersymbol interference. This is special serious in the High Speed Digital System. To reduce this problem, adaptive equalizer is used in receiver. This article is going to introduce adaptive equalizer signal processing algorithms in the fast fading condition.